Whole-Exome Sequencing Reveals a Rare Variant of OTOF Gene Causing Congenital Non-syndromic Hearing Loss Among Large Muslim Families Favoring Consanguinity - Fareed, Mohd; Sharma, Varun; Singh, Inderpal; Rehman, Sayeed Ur; Singh, Gurdarshan; Afzal, Mohammad (Frontiers in Genetics, 2021)
Non-syndromic hearing loss (NSHL) is one of the most frequent auditory deficits in humans characterized by high clinical and genetic heterogeneity. Very few studies have reported the relationship between OTOF (Locus: DFNB9) and hereditary hearing loss in India. We aimed to decipher the genetic cause of prelingual NSHL in a large affected Muslim consanguineous families using whole-exome sequencing (WES). The study was performed following the guidelines and regulations of the Indian Council of Medical Research (ICMR), New Delhi. The population was identified from Jammu and Kashmir, the Northernmost part of India. Near about 100 individuals were born deaf-mute in the village of 3,000 inhabitants. A total of 103 individuals (with 52 cases and 51 controls) agreed to participate in this study. Our study revealed a rare nonsense homozygous mutation NC_000002.11:g.2:26702224G>A; NM_001287489.2:c.2122C>T; NP_001274418.1:p.(Arg708*) in the 18th exon of the OTOF gene. Our study provides the first insight into this homozygous condition, which has not been previously reported in ExAC, 1000Genome and genomAD databases. Furthermore, the variant was confirmed in the population cohort (n = 103) using Sanger sequencing. In addition to the pathogenic OTOF variant, the WES data also revealed novel and recurrent mutations in CDH23, GJB2, MYO15A, OTOG, SLC26A4 genes. The rare pathogenic and the novel variants observed in this study have been submitted to the ClinVar database and are publicly available online with the accessions SCV001448680.1, SCV001448682.1 and SCV001448681.1. We conclude that OTOF-related NSHL hearing loss is prevalent in the region due to successive inbreeding in its generations. We recommend premarital genetic testing and genetic counseling strategies to minimize and control the disease risk in future generations.